The Impact of Human Resource Management on Financial Performance: A Case Study in the Manufacturing Industry - Reza Rahmadi Hasibuan; Sabil, Sabil; Mutia Pamikatsih; Elok Ainur Latif (International Journal of Technology and Education Research, 2024)
The management of human resources (HR) is a crucial aspect that significantly contributes to the financial performance of a company, especially in the manufacturing industry. This industry, characterized by its labor-intensive and technology-driven nature, requires effective HR management to optimize productivity and operational efficiency. This study aims to assess how various HRM practices, such as recruitment, training, development, and employee retention, influence financial performance. This type of research uses a quantitative approach. This research will investigate the effect of human resource management on financial performance using numerical calculations, so that the data collected will be in the form of numbers (score, ranking, frequency). This data will be analyzed using statistics to answer certain questions or hypotheses, making it a quantitative study. The research subjects were employees of manufacturing companies, with a population of 120 people. The sample is part of the population that is the research subject. From the results of the calculations above, it can be explained that human resource management has a significant and positive effect on financial performance. This can be seen from the calculated significant value of 0.000 which is smaller than the alpha value of 0.05.